Holiness As Perfection in Love: The Christian Sense - Omernick, Kenneth E (Journal of Dharma, 1983)
Like the door to a building or light during the day, we have become so used to the presence of some realities that we take them for granted. Though they are necessary it seldom occurs to us to question why they are there or what they mean. In the history of spirituality, the "call to holiness" has often been associated with Matthew 5 : 48 : "Be perfect as your heavenly Father is perfect." It is one of those scriptural "realities" which "should be there" or ’immediately come to mind" when talking about Christian moral development or sanctity. So, from the monastics to Francis of Assisi and Francis de Sales, to the Protestant reformers and John Wesley, this passage had held a fascination for many and even inspired a theology of "perfection.’